Don't Hold Your Breath—A Video-Based Study of Procedural Intervals During Pediatric Rapid Sequence Intubation. Issue 2 (2nd February 2022) - Shah, Ashish; Edmunds, Katherine; Dean, Preston; Frey, Mary; Boyd, Stephanie; Ahaus, Karen; Zhang, Yin; Varadarajan, Kartik; Kerrey, Benjamin T.
Abstract : Objective: Develop a framework for data collection to determine the contributions of both laryngoscopy and tube delivery intervals to the apneic period in unsuccessful and successful attempts among patients undergoing rapid sequence intubation (RSI) in a pediatric emergency department (PED). Design: This was a retrospective, observational study of RSI. Setting: An academic PED. Patients: A consecutive sample of all intubations attempts of first provider physicians performing RSI in the shock trauma suite over a 10-month period in 2018–2019. Measurement and Main Results: Data were collected by structured video review. The main outcome was the duration of the laryngoscopy and tube delivery intervals per attempt. We compared interval duration between successful and unsuccessful attempts, adjusting for age, accounting for repeated measures, and clustering by provider. There were 69 patients with 89 total intubation attempts. Sixty-three patients were successfully intubated by the first provider (91%). Pediatric emergency medicine fellows performed 54% of the attempts. The median duration of the apneic period per attempt was longer in unsuccessful attempts (57 vs 44 seconds; median of difference, −10.5; 95% confidence interval [CI], −17.0 to −4.0). The duration of laryngoscopy was similar (18 vs 13 seconds; median of difference, −3.5; 95% CI, −8.0 to 1.0), but tube delivery was longer in unsuccessful attempts (25.5 vs. 11 seconds; median of difference, −12.5; 95% CI, −17.0 to −4.0). These results did not change when adjusting for age or clustering by provider. Conclusions: We successfully developed a specific, time-based framework for the contributors to prolonged apnea in RSI. Prolonged tube delivery accounted for more of the apneic period. Future studies and improvement should focus on problems during tube delivery in the PED.